Sexual behaviors among methadone maintenance patients in a mountainous area in northern Vietnam - Boggiano, Victoria L. (2017)
Background: Methadone maintenance treatment (MMT) improves patients’ ability to access HIV-related services and reduces needle sharing and other risky HIV-related behaviors. However, patients may continue to engage in risky sexual practices. In this study, we evaluate sexual behaviors of MMT patients in a mountainous province in Northern Vietnam. Methods: We explored the health status, MMT and substance use history, and sexual practices of 241 male MMT patients in Tuyen Quang province. Health status was investigated using the EuroQOL-5 Dimensions-5 Levels (EQ-5D-5 L). Multivariate logistic regression was employed to assess associated factors. Results: Most patients (66.4%) reported having at least one sexual partner within the previous twelve months. Most of these partners were spouses or primary partners (72.6%). About 8.3% of patients had casual partners, and 5.8% had visited sex workers; of those who engaged in casual sexual relationships, 90.9% reported using condoms. Current drug use and living in a remote area were associated with an increased odd of having two or more sexual partners, while anxiety or depression was associated with lower odds. Conclusion: This study highlights a low proportion of having sexual risk behaviors among MMT patients in Vietnamese mountainous settings. Integrating education about safe sexual practices into MMT services, along with providing medical care and ensuring methadone treatment adherence, is an important component in HIV risk reduction for these patients who were at risk of unsafe sexual practices.